The in situ growth of Cu2O with a honeycomb structure on a roughed graphite paper for the efficient electroreduction of CO2 to C2H4. Issue 20 (21st September 2021) - Yan, Zuoyu; Wang, Xiuxiu; Tan, Yang; Liu, Aihua; Luo, Fenqiang; Zhang, Miaorong; Zeng, Lingxing; Zhang, Yan
Abstract : A Cu2 O/NGP self-supporting electrocatalyst is used for the electrocatalytic reduction of CO2 to ethylene to solve environmental and energy problems. Abstract : Metals and their alloy-based electrocatalysts continue to attract considerable attention for electrochemical carbon dioxide reduction reactions (CO2 RRs). In this work, cuprous oxide (Cu2 O) was supported on N-doped flexible roughed graphite paper (NGP) to fabricate Cu2 O/NGP self-supporting electrocatalysts for CO2 RRs by electrodeposition and heat treatment. In the Cu2 O/NGP electrocatalyst, NGP acted as a current collector and conducting channel, which can effectively transfer electrons from the active sites of Cu2 O to NGP, and thus, enhance the catalytic performance of Cu2 O/NGP for CO2 RRs. The overall Faradaic efficiency of Cu2 O/NGP for CO2 RRs reached 96% at −0.9 V vs. reversible hydrogen electrode, of which 35% originated from yielding ethylene (C2 H4 ), suggesting its high activity and C2 H4 selectivity. Furthermore, the excellent stability of Cu2 O/NGP over 10 h made it preferable as an effective electrocatalyst for CO2 RRs. The good electrocatalytic performance could be attributed to the unique self-supporting structure and the synergetic effect between Cu2 O and NGP.